Phytochemical Studies of Mesua Corneri (Linn.) and Garcinia Mangostana (Linn.) and Their Biological Activities - Sheikh Mohd Ghazali, Sheikh Ahmad Izaddin (2006)
Roots of Garcinia mangostana L. and the stem bark of Mesua corneri L. were chemically investigated. Detail phytochemical studies on the roots of Garcinia mangostana L. and the stem bark of Mesua corneri L. have resulted in the isolation of eleven compounds. The structures of these compounds were elucidated using spectroscopic experiments namely NMR, IR, UV and MS. The root bark of Garcinia mangostana L. furnished six xanthones, a-mangostin, Pmangostin, y-mangostin, garcinone-D, mangostanol and gartanin. Up to now, research has only been carried out on the fruit hull and the stem bark of this plant. There have been no studies yet on the root bark of Garcinia wangostana L. Meanwhile, investigations on stem bark of Mesua corneri L gave three triterpenoid, stigmasterol,fridelin, friedelan-1,3-dione and two xanthones, rubraxanthone and Inophyilin B. So far, there has been no reports at all on this plant. The crude hexane and chloroform extracts of Mesua corneri L. stem bark were active against HL-60 cell line with 1Cj0 values of less than 30 pg/ml. The crude hexane and chloroform extracts of Garcinia mangostana L. root bark were found to be active against CEM-SS cells line with ICsO values of less than 30 pglml. Meanwhile, the y-mangostin gave a significant activity with an ICjO value of 4.7 pglml. This is a new activity for this plant. The antimicrobial assay was carried out towards four pathogenic bacteria, Methicillin Resistant Staphylococcus awes, Pseudornonas aeruginosa, Salmonella typhiinurium and Bacillus subtilis. Most of the crude extracts tested against these microbes gave only moderate or weak activities. The larvicidal tests performed against the larvae of Aedes aegypti. The crude hexane and chloroform extracts of Garcinia mangostana L. showed a strong activity against the larvae with LC50 values of less than 100 pglml. The pure compounds a-mangostin and ymangostin gave good activities with LCso value of 18.4 and 32.4 pglml respectively .The crude hexane and choloroform extracts of Mesua corneri L. showed a good activities against the larvae and gave LCSo values of less than 100 pgjrnl. Rubraxanthone showed a strong activity against the larvae with a LCso value of 18.4 pglml. These activities have not been reported before and this is a new finding.The antifungal activity testing of the plant extracts were carried out against the fungi Candida albican, Aspergillus ochraceaus, Sacchoromyces cerevisiae and Candida lypolytica. No activity was observed for all the crude extracts.